Diversity of indicator microorganisms in the evaluation of sea recreational beach sand fecal contamination: current knowledge and perspectives - Bartelochi Pinto, Aline; Fernandes Cardoso de Oliveira, Ana Julia (O Mundo da Saúde, 2011)
Although the quality of sea recreational waters is already monitored by programs implanted in some Brazilian states, including the State São Paulo, little attention has been given to beach sands, which have been disregarded from the point of view of public health. However, this panorama is changing in recent years due to an increasing number of cases of mycoses and bacterial infections affecting people who frequent beaches and use sands as recreation places. This has caused greater concerns with the contamination of this environment, also measurable by the increase of the number of scientific works on sediments and recreational beach sands microbiota. Currently one knows that in general these sediments contain more microorganisms than the water and are therefore potential sources of contamination of human beings by pathogenic microorganisms. The results of works carried through in some countries are worrying, and have demonstrated the necessity of establishing standards and limits so that monitoring programs of the microbiological quality of beach sands are implanted. Such concern is especially high in Brazil, a country of a tropical climate where thousands of beaches, used for recreation, extend for almost eight thousand kilometers of the coast. In the context of Baixada Santista, studies carried through have shown that in certain situations beach sands can contain more microorganisms than waters and may be a risk to the health of users.